Low and high orders light scattering within the dispersible media. - Berrocal, Edouard; Romanov, V. P.; Churmakov, D. Y.; Meglinski, I. V. (Cranfield University, 2005)
Sprays, aerosols as well as other industrially relevant turbid media can be characterized by light scattering techniques. However these techniques often fall into the intermediate scattering regime where the average number of times a photon is scattered is too great for single scattering to be assumed, but too few for the diffusion approximation to be applied. We present the results of theoretical study provided details of scattering of laser radiation in the intermediate single-tomultiple scattering regime. Crossed fiber optic source- detector geometry is considered to separate the intensity of single scattering from higher scattering orders. A quantitative analysis of scattering orders in the intermediate single-tomultiple scattering regime is presented. Agreement between the analytical and Monte Carlo techniques both used for the calculation of double light scattering intensity is demonstrated. Influence of detector numerical aperture on the scattering orders is shown for the intermediate single-to-multiple scattering regime. The method used can be applied to verify analytical results indirectly against experiment via Monte Carlo calculations that include the imperfections of the experiment.